The Bam Element of Tiv Culture: Opportunities and Challenges - ITYONZUGHUL, Thaddeus (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
There is a substantial amount of existing material about the Tiv culture of central Nigeria. However, none of this work focuses specifically on the opportunities and challenges presented by the Tiv Bam. In this way, this study intervenes to narrow the existing void in historical literature. The research analyses the notions of Bam using primary and secondary sources of data. It establishes Bam’s historical background and investigates its modus operandi. The benefits and challenges of Bam are also evaluated, including inadequate record keeping, a negative attitude towards loan payback, paucity of funds, illiteracy, and an unwritten constitution. Despite the aforementioned and related problems, it has nonetheless assisted the members in doing what they could not accomplish individually. The conclusion is that for Bam to have a greater impact on the Tiv, the aforementioned hurdles must be overcome.